Is Low Positive JAK2 V617F Mutation Test Result Clinically Significant?: Multi-Institutional Study. Issue 8 (September 2016) - Wu, Xiaojun; Lee, Joong Won; Peker, Deniz; Spitzer, Silvia G.; Laser, Jordan; Reddy, Vishnu V.B.; Harada, Shuko
Abstract : Objectives: Acquired somatic mutation Janus kinase 2 ( JAK2 ) V617F is associated with various myeloproliferative neoplasms (MPN). Allele-specific real-time polymerase chain reaction has been widely adopted to detect mutation; however, the utility of low positive results is not well understood. The aim of this study is to investigate the clinical significance of low positivity of JAK2 V617F. Materials and Methods: Retrospective analysis was performed for JAK2 V617F mutation tests performed using JAK2 MutaQuant kit (Ipsogen) in molecular laboratories at 2 major academic medical centers between 2010 and 2012. Cases with low positive JAK2 V617F, defined as 0.2% to 5% mutant allele, were documented. Chart review was performed for the clinical correlation. Results: A total of 1697 JAK2 V617F tests was performed. Forty-five cases (2.65%) yielded a low JAK2 V617F positivity (average 1.45%), the majority of which (n=26, 62%) had <1%. Eight cases had a history of MPN. The remaining cases were related to reactive conditions without a clonal disease. Our data indicate that a low positivity of JAK2 V617F can be seen in MPN as well as reactive conditions. Conclusions: An interpretation of JAK2 V617F status should not be performed simply following some arbitrary cutoff. Any low positivity of JAK2 V617F should be reported and a correlation with clinical information is warranted for proper interpretation.